2017
DOI: 10.1016/j.rmed.2017.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone for acute exacerbation of idiopathic pulmonary fibrosis: A retrospective study

Abstract: A regimen of pirfenidone combined with corticosteroids and rhTM may improve survival in patients with AE-IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
1
19
0
3
Order By: Relevance
“…Under this technique, weights were the inverse of (1 − propensity score) for patients receiving rhTM (rhTM arm) and the inverse of the propensity score for patients not receiving rhTM (control arm). The propensity score was estimated using multivariable logistic regression analysis including the seven most clinically relevant variables known to be possible confounders: IPF/non‐IPF, disease severity (mild/severe), prednisolone administration and anti‐fibrotic therapy using pirfenidone and/or nintedanib in the stable state, HRCT pattern (diffuse/non‐diffuse) , PaO 2 /FiO 2 ratio (≤200/>200) and the level of Krebs von den Lungen (KL)‐6 at AE. Adjusted hazard ratios (HR) with 95% CI were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Under this technique, weights were the inverse of (1 − propensity score) for patients receiving rhTM (rhTM arm) and the inverse of the propensity score for patients not receiving rhTM (control arm). The propensity score was estimated using multivariable logistic regression analysis including the seven most clinically relevant variables known to be possible confounders: IPF/non‐IPF, disease severity (mild/severe), prednisolone administration and anti‐fibrotic therapy using pirfenidone and/or nintedanib in the stable state, HRCT pattern (diffuse/non‐diffuse) , PaO 2 /FiO 2 ratio (≤200/>200) and the level of Krebs von den Lungen (KL)‐6 at AE. Adjusted hazard ratios (HR) with 95% CI were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Previous retrospective studies have described the potential benefit of immunosuppressive therapies for AE‐IPF, including cyclosporine A, tacrolimus and rituximab, plasma exchange and intravenous immunoglobulin . Meanwhile, the survival benefit of adding non‐immunosuppressive therapies, including polymyxin‐B‐immobilized fibre column haemoperfusion, recombinant thrombomodulin, azithromycin and pirfenidone has also been reported, although high‐dose CS was the mainstay therapy in almost all these studies. Interestingly, a recent retrospective study by Papiris et al has shown that, by applying the non‐steroid approach, including supportive care and appropriate antimicrobials, half of the patients with AE‐IPF survived .…”
Section: Discussionmentioning
confidence: 99%
“…Furuya et al found that among 47 cases of AE-IPF (all treated with high dose corticosteroid and some with NAC, CTX/CsA or rhTM), the 3 monthsurvival rate was significantly better in 20 patients receiving pirfenidone than in 27 patients not receiving pirfenidone (55% vs. 34%, P ¼ 0.042). Among the patients receiving rhTM (N ¼ 22), pirfenidone did not make significant difference in the outcome (80% vs. 42%, P ¼ 0.067) (Furuya et al, 2017). In univariate analysis, nonuse of rhTM was a potential risk factor for death (hazard ratio [HR], 3.717; P ¼ 0.035).…”
Section: Antifibrotic Drugsmentioning
confidence: 98%